"نظم المعلومات المحاسبیة في بیئة التحول الرقمي– الواقع والتحدیات - دراسة میدانیة -" - زكية, بن عيشة; منى, عثماني; عبد الرزاق, مشارة; عماد, محتالي (University of eloued جامعة الوادي, 2021)
"هدفت الدراسة إلى إبراز الإطار النظري للتحول الرقمي من جهة ومن جهة أخرى كيف ساهم ذلك في نظم المعلومات المحاسبية، مع عرض لأهم مظاهر التحول الرقمي التي ساهمت في تطوير نظم المعلومات تلك مثل تقنية سلسلة الكتل، الذكاء الاصطناعي، العقود الذكية... الخ. تمت الدراسة من خلال محاولة الإجابة على الإشكالية الرئيسية التالية: ما هو واقع نظم المعلومات المحاسبة في بيئة التحول الرقمي، وما هي التحديات التي تواجهها؟. تم معالجة الموضوع من خلال شقين أحدهما نظري وآخر تطبيقي، ففي الجانب النظري تم التعرف على ماهية التحول الرقمي ومختلف التقنيات التي تقدمها لمنظمات الأعمال، كما تم التطرق إلى نظم المعلومات المحاسبية وكيف استفادت من مختلف تقنيات التحول الرقمي؛ أما في الجانب التطبيقي فقد تم إسقاط المعارف النظرية على الواقع العملي باستخدام المنهج الوصفي التحليلي. تمثلت أداة الدراسة في استبيان موزع على عينة من 86فرد من خبراء في مجال المحاسبة إلى جانب مسيرين لمؤسسات اقتصادية في ولاية الوادي، وقد تم التوصل إلى أن هناك درجة عالية الوعي بمزايا التحول الرقمي ضمن نظم المعلومات المحاسبية كما يوجد توجه بدرجة عالية نحو تعزيز ممارسات التحول الرقمي ضمن نظم المعلومات المحاسبية من جهة، كما تواجه منظمات الأعمال تلك درجة منخفضة من التحديات في سبيل تطوير نظم المعلومات المحاسبية بما يتلاءم مع معطيات التحول الرقمي من جهة أخرى.""The study aims to highlight the theoretical framework of digital transformation, and how it contributed to accounting information systems, with a presentation of the most important aspects of digital transformation that contributed to the development of such information systems such as block chain technology, artificial intelligence, smart contracts... etc. The study was conducted by attempting to answer the following main problem: What is the reality of accounting information systems in the digital transformation environment, and what are the challenges it faces? The topic was addressed through two parts, one theoretical and the other applied. On the theoretical side, the nature of digital transformation and the various technologies it offers to business organizations were identified. Accounting information systems were also addressed and how they benefited from various digital transformation techniques. As for the practical side, the theoretical knowledge was projected onto the practical reality by using the descriptive analytical method. The study tool was represented in a questionnaire distributed to a sample of 86 individuals from experts in the field of accounting as well as managers of economic institutions in El-Oued. Digital within the accounting information systems on the one hand, and these business organizations face a low degree of challenges in order to develop accounting information systems in line with the digital transformation data on the other hand."
مذكرة ماستر تدقيق محاسبي
Keywords: تحول رقمي؛ نظم معلومات محاسبية; Digital Transformation; Accounting Information Systems.